2014
DOI: 10.1186/1475-2859-13-31
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial degradation of chlorophenols and their derivatives

Abstract: Chlorophenols (CPs) and their derivatives are persistent environmental pollutants which are used in the manufacture of dyes, drugs, pesticides and other industrial products. CPs, which include monochlorophenols, polychlorophenols, chloronitrophenols, chloroaminophenols and chloromethylphenols, are highly toxic to living beings due to their carcinogenic, mutagenic and cytotoxic properties. Several physico-chemical and biological methods have been used for removal of CPs from the environment. Bacterial degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
137
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(140 citation statements)
references
References 133 publications
2
137
1
Order By: Relevance
“…Several reviews concerning various aspects of bacterial degradation of chlorophenols (Arora & Bae, 2014;Olaniran & Igbinosa, 2011), nitrophenols , and alkylphenols have been recently published. Our review is focused mainly on the genetic basis of the bacterial degradation of phenol and its derivatives, and on the regulation of these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews concerning various aspects of bacterial degradation of chlorophenols (Arora & Bae, 2014;Olaniran & Igbinosa, 2011), nitrophenols , and alkylphenols have been recently published. Our review is focused mainly on the genetic basis of the bacterial degradation of phenol and its derivatives, and on the regulation of these processes.…”
Section: Introductionmentioning
confidence: 99%
“…This oxidative dehalogenation is often catalyzed by flavin-dependent monooxygenases (20). These oxygenases include both types of monooxygenases, those that utilize a single protein as well as those that utilize two proteins.…”
mentioning
confidence: 99%
“…Subordinate peaks observed at m/z 149, m/z 121, m/z 76 and m/z 73 in mass-spectra corresponding to different retention times were of L-methionine, alpha-methylbenzylamine, glycolic acid and isobutylamine respectively. Arora and Bae [47] reported that the anaerobic bacterial treatment of 2,4-dichloro phenol and 2-chloro phenol resulted in the formation of 4-hydroxybenzoic acid as an intermediate in different reaction pathways. In our earlier work [25], 4-hydroxybenzoic acid, D-glucuronic acid, maleic acid/fumaric acid and L-alanine has been identified as the major intermediates during the degradation of 4C2AP using the combined treatment of hydrodynamic cavitation, UV photolysis and ozone.…”
Section: Identification Of Intermediatesmentioning
confidence: 99%